TEKANAN PENDUDUK TERHADAP ZONA REHABILITASI TAMAN NASIONAL MERU BETIRI JEMBER JAWA TIMUR - , SAMSUL HADI, Dr. Ir. Lies Rahayu W.F., MP. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
One problem of national park management is threat of total population pressure. Management of rehabilitation zone of Meru Betiri National Park also faces problem of population pressure around local society. So that, population pressure and dependence rate around the local society against rehabilitation zone may be a study in structuring strategy of rehabilitation zone management. Population pressure on national park conservation is estimated to increase continuously, so that it is necessary to make various efforts associated with increasing of economic role of national park in improving society prosperity around the area. This study intends to: (1) understand population pressure (PP) on rehabilitation zone